PENGARUH MARKET DAN LEARNING ORIENTATIONS TERHADAP RELATIONAL CAPABILITY DAN KINERJA USAHA UMKM DI KOTA MATARAM - Sulhaini Sulhaini; Rusdan Rusdan; Sulaimiah Sulaimiah; Baiq Ismiwati; Rahman Dayani; Rini Anggriani (Master of Management, Mataram University, 2018)
The objective of the study is to examine the effect of organisational culture, i.e learning and market orientations toward relational capability and business performance of SMEs. The samples were purposively selected in the city of Mataram, they must have at least four employess. They were door-to-door approached during a four-week data collection period. The findings suggested that the orientations strengthen SMEs’ relational capability and performance. Nonetheless, learning orientation does not guarantee better business performance unless the orientation is strongly implemented intofirms’ relational capability. The study provides interesting contributions toward relationship marketing literature by giving evidences regarding the effects of the cultural orientations on SMEs’ relational capability and perfromance.Founding of SMEs should emphasise on the development and implementation of learning and market orientations to improve their relational capability and performance.Keywords: learning orientation, market orientation, relational capability, business performance